Peran Guru Dalam Mencegah Dan Mengatasi Brain Rot Pada Siswa - Abdul Aziz, Nurdin (CV RIFAINSTITUT, 2025)
The phenomenon of brain rot has silently crept into classrooms—students are physically present, yet their minds wander through the corridors of algorithms and instant entertainment. In this context, teachers are no longer mere transmitters of knowledge but guardians of awareness. This study explores the role of teachers in preventing and addressing brain rot—a condition marked by cognitive decline and reduced attention span caused by excessive exposure to shallow digital content. Using a descriptive qualitative approach, the research examines pedagogical strategies that are humanistic, reflective, and adaptive to the challenges of the digital age. The findings reveal that teachers hold a strategic position as curators of meaning: guiding students not only to consume information but also to transform it into understanding. These efforts include fostering deep literacy habits, implementing dialogue-based learning, and creating learning environments that nurture self-awareness and empathy. Thus, the teacher’s role extends beyond the transfer of knowledge—toward becoming a guardian who ensures that reason and mindfulness continue to grow amid the flood of digital distractions.